Quantifying boron and phosphorous dopant concentrations in silicon from photoluminescence spectroscopy at 79 K. Issue 11 (4th July 2016) - Liu, AnYao; Nguyen, Hieu T.; Macdonald, Daniel
Abstract : Photoluminescence spectroscopy at 79 K is shown to provide an alternative, non‐destructive characterisation method for quantifying the boron and phosphorous dopant concentrations in silicon. The dopant concentrations are revealed by the photoluminescence intensity ratios of the dopant‐related features to the band‐to‐band recombination peaks. The intensity ratio is found to be insensitive to the excitation power in a wide range of 0.3 W cm −2 –100 kW cm −2 . Calibration curves for boron and phosphorous in silicon are presented for [B] below 5 × 10 17 cm −3 and [P] below 8 × 10 16 cm −3 .